2022
DOI: 10.1111/jbi.14381
|View full text |Cite
|
Sign up to set email alerts
|

Microbial stowaways: Waterbirds as dispersal vectors of aquatic pro‐ and microeukaryotic communities

Abstract: Aim Waterbirds are important dispersal vectors of multicellular organisms; however, no study to date has focused on their potential role in dispersing aquatic microbial communities. We explicitly studied endozoochory of prokaryotes and unicellular microeukaryotes by waterbirds using DNA metabarcoding. By directly comparing the dispersed set of organisms to the source pool of a natural metacommunity, we aimed at a realistic estimate of the importance of waterbird zoochory for natural microbial communities. Loca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 109 publications
0
26
0
Order By: Relevance
“…In the future, there needs to be far more research into microbial dispersal by waterbirds. In particular, there is a need to further clarify which of the microbes detected in barcoding studies of faeces or feathers are viable, and what influence the microbes carried by birds have on pre‐established microbial communities, compared to inputs from air or water (Custer et al, 2022; Szabó et al, 2022). The meta‐gut concept should be explored, comparing gut microbiomes of waterbirds and co‐existing aquatic organisms (Dutton et al, 2021).…”
Section: Understudied Role Of Waterbirds As Vectors For Microbesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, there needs to be far more research into microbial dispersal by waterbirds. In particular, there is a need to further clarify which of the microbes detected in barcoding studies of faeces or feathers are viable, and what influence the microbes carried by birds have on pre‐established microbial communities, compared to inputs from air or water (Custer et al, 2022; Szabó et al, 2022). The meta‐gut concept should be explored, comparing gut microbiomes of waterbirds and co‐existing aquatic organisms (Dutton et al, 2021).…”
Section: Understudied Role Of Waterbirds As Vectors For Microbesmentioning
confidence: 99%
“…Like the nostrils of seabirds (Brito-Echeverria et al, 2009), the feathers of flamingos are rich in haloarchaea, which presumably disperse with flamingos when they undergo long-distance movements (Yim et al, 2015). There is evidence for major exchange between the microbial communities carried in waterbird guts and those present in the lakes they visit (Szabó et al, 2022), suggesting that waterbirds may be vital in maintaining connectivity in microbial lake metacommunities, and that their gut microbiomes might influence lake biogeochemistry, as well as the gut microbiomes of other aquatic organisms (the "meta-gut" concept; Dutton et al, 2021).…”
Section: Under S Tudied Role Of Waterb Irds a S Vec Tor S For Microb E Smentioning
confidence: 99%
“…Our results demonstrated that soda pans host diverse microbial communities, which were so far largely unexplored due to the lack of regional studies and the limited application of molecular methods. Even though these unique and regionally restricted ecosystems serve as important refuges for a number of rare or endangered species (Horváth et al ., 2013; Stenger-Kovács and Lengyel, 2015), and serve as important feeding sites for waterbirds (Boros et al ., 2017; Szabó et al ., 2022), they are critically endangered by climate change (Horváth et al ., 2019). The ongoing environmental changes will most likely lead to biodiversity loss in multiple microbial groups according to our results, which might induce critical ecosystem-level consequences.…”
Section: Discussionmentioning
confidence: 99%
“…For the determination of prokaryotic and eukaryotic community composition, the V4 region of the 16S rRNA gene and the V7 region of the 18S rRNA gene were amplified, using prokaryotic primers EMBf 515F (GTGYCAGCMGCCGCGGTAA, Parada, Needham and Fuhrman, 2016) – EMBr 806R (GGACTACNVGGGTWTCTAAT, Apprill et al ., 2015) and eukaryotic primers UnivF-1183mod (AATTTGACTCAACRCGGG) – UnivR-1443mod (GRGCATCACAGACCTG, Ray et al ., 2016). All polymerase chain reactions and amplicon sequencing (Illumina MiSeq platform) were carried out by LGC Genomics (Berlin, Germany) following the steps described in Szabó et al ., 2022 (Table S3).…”
Section: Methodsmentioning
confidence: 99%
“…However, it is unknown how urotrichs are dispersed among water bodies as cyst formation has so far never been observed. We therefore exclude wind drift, but a direct transport in water drops or faeces via birds (Szabó et al, 2022) may be possible as birds were occasionally seen at the mountain reservoirs. Alternatively, urotrichs could be washed out from the vegetation cover in the surroundings of the mountain reservoirs as, for example, in seepage and fen areas of the Rotmoos valley near the SWH, urotrichs were frequently observed (Sonntag, unpublished).…”
Section: Discussionmentioning
confidence: 99%